Hubungan antara Transformational Leadership dan Quality of Work Life dengan Employee Engagement pada Generasi Z - Simatupang, Jeremia; Satwika, Pratista Arya (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2024)
Generation Z is the generation that's less engaged in the workplace. Transformational leadership and quality of work life are two of the other factors that can affect employee engagement. This research aims to find out the relationship between transformational leadership and the quality of work life simultaneously and partially towards employee engagement. Participants of this research are 60 employees of generation z at PT. Kalimantan Prima Persada. Simple random sampling was used to select employees with the criteria of Generation Z employees and permanent employees. The instrument for data collection used a scale of employee engagement with reliability 0.911, and then a scale of transformational leadership with reliability 0.953, and scale of quality of work life with reliability 0.842. This research using online questionnaires for data collection, and data analysis techniques using multiple linear regression. The result of correlation between variables is R 0.667. The results show that there is a relationship between transformational leadership and the quality of work life both simultaneously and partially towards employee engagement. Therefore, it would be useful for companies to increase their employee engagement.